THE SERBIAN ELECTIONS ACT OF 1870: AN ASSEMBLY’S THOUGHTS ON PARLIAMENTARY ELECTIONS - Kršljanin, Nina (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
The Constitution of Serbia of 1869 (the so-called Regency Constitution) was the first Serbian constitution to give the Parliament (National Assembly) legislative powers, albeit inferior to those of the monarch. However, many important details regarding the parliamentary elections were not specified by the Constitution: for example, the length of the MPs’ term or the question of whether the ballots should be secret or public. Due to various political reasons at the time of the passing of the Constitution, these issues were left to later legislation. Accordingly, the aforementioned and other matters were specified in the Elections Act of 1870, passed by the very first legislative assembly itself. This paper will analyse the Elections Act itself and the debates in the National Assembly during its passing. It will particularly focus on issues that were hotly debated in the Assembly, as well as those where the Elections Act introduces a significant change to the constitutional framework. Finally, it will strive to explain the reasons for the introduction of particular institutions and to show how their creators (and opponents) expected them to influence the development of the Serbian Parliament.